Penyelenggaraan Pengembangan Produk Layanan Perbankan Berupa BNI Mobile Remittance - Cathleya Anjani Pramodawarddhani (UNES Law Review, 2023)
Technological developments have a major influence on the banking world, one of which is remittance activities. With the rapid development of technology, one of the banks in Indonesia wants to create a remittance service application called BNI Mobile Remittance developed by BNI Singapore Overseas Branch Office (KCLN). Based on this description, the author is interested in discussing further about how to carry out the development of banking products in the form of BNI Mobile Remittance in accordance with applicable laws and regulations and their obstacles? This research is a normative research supported by interviews with related resource persons using primary and secondary data. The results of this research are that the implementation of BNI Mobile Remittance banking product development can be carried out after obtaining approval from the Financial Services Authority where the approval will be given after BNI meets the requirements set out, but obstacles in licensing the implementation of BNI Mobile Remittance are discrepancies in the licensing which is other than Financial Services Authority, BNI needs to obtain additional approval from Bank Indonesia and there is ambiguity over the status given by Financial Services Authority in submitting the product. In the system, the BNI Mobile Remittance permit application only states that "we have received the application file", not "application approved".